Die Verband tussen etiese orientasie en die beoordeling van wenslikheid van oudio visuele erotiek en sensuur - André Van Deventer; H J Breytenbach H J Breytenbach (Communicare)
It seems that distinct differences of opinion regarding the desirability of the portrayal of eroticism in films and the application of censorship are evident in the South African society. This empirical study has attempted to identify amongst young adults the role that their ethical orientation plays in evaluating film eroticism and censorship. For this purpose four ethical orientations (the Individualistically, Transcendentalistically, Relativistically and Altruistically orientated groups) were identified. Research was conducted at four universities in which 418 respondents participated. The most important findings were that respondents supporting the Transcendentalistic ethical orienta tion differed significantly from the other in displaying a more negative attitude towards film eroticism and a more positive view of censorship. It was concluded that researchers should thoroughly take cognisance of the role that respondents' ethical red by the Publisher (dated 2010).